2022
DOI: 10.1111/irel.12324
|View full text |Cite
|
Sign up to set email alerts
|

Does robotization affect job quality? Evidence from European regional labor markets

Abstract: Whereas there are recent papers on the effect of robot adoption on employment and wages, there is no evidence on how robots affect non‐monetary working conditions. We explore the impact of robot adoption on several domains of non‐monetary working conditions in Europe over the period 1995–2005 combining information from the World Robotics Survey and the European Working Conditions Survey. In order to deal with the possible endogeneity of robot deployment, we employ an instrumental variables strategy, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…Jointly with the recent evidence emphasising workers' valuation of non-monetary job amenities and the persistent controversies about economic convergence and the decoupling of productivity from wages, it seems advisable to support a larger role for the analysis of working conditions in both academic research and policymaking. This issue might be particularly relevant for addressing the impact of globalisation and technology on labour markets, where, apart from noticeable exceptions (Ant on et al, 2022;Menon et al, 2019), non-monetary job features have received relatively little attention. Notes 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jointly with the recent evidence emphasising workers' valuation of non-monetary job amenities and the persistent controversies about economic convergence and the decoupling of productivity from wages, it seems advisable to support a larger role for the analysis of working conditions in both academic research and policymaking. This issue might be particularly relevant for addressing the impact of globalisation and technology on labour markets, where, apart from noticeable exceptions (Ant on et al, 2022;Menon et al, 2019), non-monetary job features have received relatively little attention. Notes 1.…”
Section: Discussionmentioning
confidence: 99%
“…As in most of the recent works using these sorts of indexes (see, e.g. Green et al , 2013; Menon et al , 2019 and Antón et al , 2022), each variable receives the same weight within each sub-dimension and we assign the same importance to each sub-dimension when computing the average value for each dimension. Sensitivity analyses in Muñoz de Bustillo et al (2011a) suggest that the composite measures of these dimensions are quite robust to the use of different weighting schemes, because there is a high positive correlation between the outcomes in different domains.…”
Section: Notesmentioning
confidence: 99%
“…Anto ´n et al (2020) found that robotization significantly improved work intensity but had no effect on the physical environment, skills or discretion [4]. Nevertheless, it is worth mentioning that their data did not allow them to examine the effect of robotization on wage to fully assess the possibility that the high salary compensates for other deficiencies.…”
Section: Literatures Reviewsmentioning
confidence: 99%
“…While improving work efficiency, robots have also shocked the job market to some extent. Some scholars believe that robots will not only reduce the number of jobs [1][2][3], but also negatively affect work intensity [4]. This idea is borne out by data from developed countries, but there is little evidence of robotization's impact in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, more-recent data has produced more-nuanced results. Antón et al (2023) consider EWCS data aggregated at the NUTS-2 level over the 1995-2005 period matched to information on industrial-robot adoption from the World Robotics Survey. Their instrumental-variables results reveal that while industrial robots have produced greater work intensity they have had no impact on the quality of workers' physical environment, skills and discretion, quantitative demands, pace or interdependence.…”
Section: Introductionmentioning
confidence: 99%